PARAMETER ESTIMATION IN A BLACK-SCHOLES MODEL - Bayram, Mustafa; Orucova Buyukoz, Gulsen; Partal, Tugcem (VINCA INST NUCLEAR SCI, 2018)
In this paper we discuss parameter estimation in black scholes model. A non-parametric estimation method and well known maximum likelihood estimator are considered. Our aim is to estimate the unknown parameters for stochastic differential equation with discrete time observation data. In simulation study we compare the non-parametric method with maximum likelihood method using stochastic numerical scheme named with Euler Maruyama.
Keywords: non-parametric estimation method; stochastic differential equations; black scholes model; maximum likelihood estimation method; PRICE; Thermodynamics